Boosting plant food polyphenol concentration by saline eustress as supplement strategies for the prevention of metabolic syndrome: an example of randomized interventional trial in the adult population - Ferrantelli, Vincenzo; Vasto, Sonya; Alongi, Angelina; Sabatino, Leo; Baldassano, Davide; Caldarella, Rosalia; Gagliano, Rosaria; Di Rosa, Luigi; Consentino, Beppe Benedetto; Vultaggio, Lorena; Baldassano, Sara (Frontiers in Nutrition, 2023)
Phenolic compounds in lettuce can increase by the application of positive stress (eustress) such as moderate saline stress. Phenolic compounds possess antioxidant capacity that is a key factor in detoxification of excess reactive oxygen species. A double blinded randomized interventional and placebo-controlled study design was carried out to compare the effect of daily dietary eustress lettuce ingestion in hepatic, lipid, bone, glucose and iron metabolism. Forty-two healthy volunteers, nineteen females and twenty-three males were divided into two groups. Participants were randomized into a polyphenol enriched treatment (PET) arm, or control arm. Each arm consumed 100 grams/day of control or eustress (polyphenols enriched treatment= PET) lettuce for twelve days. Primary study outcomes were serological analysis for assessing hepatic, lipid, bone, iron and glucose markers at baseline and after 12 days. Secondary outcomes assessed body composition. This is a provisional file, not the final typeset article Salinity stress reduced plant yield but increase caffeic (+467%) and chlorogenic (+320%) acid, as well as quercetin (+538%) and rutin (+1095%) concentration. The intake of PET lettuce reduced PTH, lowdensity lipoprotein (LDL), cholesterol, alanine transaminase (ALT) and aspartate transaminase (AST) enzymes levels and increased vitamin D and Phosphate while iron and glucose metabolism were unaffected. Supplementation with eustress lettuce by increasing polyphenols concentration ameliorates hepatic, lipid and bone homeostasis. Body composition was not affected.